2020
DOI: 10.1097/sle.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Laparoscopic Cholecystectomy in Patients With a History of Gastrectomy

Abstract: Background: Although laparoscopic cholecystectomy (LC) has been applied to patients with a history of abdominal surgery, we lack data on the surgical outcome of LC in patients with a history of gastrectomy. Here, we assessed the outcomes of LC and investigated predictive factors for conversion from laparoscopic to open surgery in patients with a gastrectomy history.Patients and Methods: We retrospectively compared the surgical outcomes of LC between patients with and without a history of gastrectomy. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…The proportion of patients who underwent gastrectomy among patients hospitalized in the ER for symptomatic cholecystitis was approximately 2.8%, which is similar to that reported in other studies [ 27 , 28 ]. It was determined that the gastrectomy did not affect the severity of inflammation or the pathology of the GB.…”
Section: Discussionsupporting
confidence: 87%
“…The proportion of patients who underwent gastrectomy among patients hospitalized in the ER for symptomatic cholecystitis was approximately 2.8%, which is similar to that reported in other studies [ 27 , 28 ]. It was determined that the gastrectomy did not affect the severity of inflammation or the pathology of the GB.…”
Section: Discussionsupporting
confidence: 87%
“…The same conclusion was also found by Zhang et al [ 20 ]. As for the postoperative hospital stays, Sasaki et al [ 19 ] and Zhang et al [ 20 ] claimed that patients with a previous gastrectomy history didn’t prolong their postoperative hospital stays, which was opposite of other research [ 16 18 , 24 ]. One of the most usual reasons for converting from LC to OC was that the previous gastrectomy history might lead to adhesions [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective study enrolled 2235 patients and revealed that patients with a previous gastrectomy history were associated with a higher conversion rate while undergoing LC surgery [ 18 ]. Some other research also found similar result [ 16 , 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations in distal pancreatectomy cohorts: Similar to pancreatoduodenectomy studies, distal pancreatectomy patients with positive drain culture have been associated with significantly higher rates of CR-POPF[ 163 , 164 ] with positive drain culture being an independent risk factor for the complication before POD3[ 165 ] and on POD4[ 166 ]. However, abdominal infection was not found to be a risk factor for CR-POPF by Sato et al [ 167 ] in their cohort of 49 patients which may have been underpowered.…”
Section: Introductionmentioning
confidence: 99%
“…most frequently in the drain fluid of CR-POPF patients. Harino et al [ 163 ] found Staphylococcus numbers to increase in patients when drains were removed after POD5, with Yang’s group reporting rapid increases in positive drain culture when drains remained between POD3 and POD7 with a prevalence of 21.6% and 73.3% respectively[ 165 ]. Hence, earlier drain removal may assist in curbing the growth of bacteria and its subsequent role in CR-POPF development.…”
Section: Introductionmentioning
confidence: 99%